Wavelength- and Time-Selective Reconfigurable Optical Add/Drop Multiplexer Using Time-Frequency Domain Processing. (29th April 2010) - Konishi Konishi, Tsuyoshi Tsuyoshi; Itoh Itoh, Ryosuke Ryosuke; Itoh Itoh, Kazuyoshi Kazuyoshi
Abstract : We propose and demonstrate a wavelength- and time-selective reconfigurable optical add/drop multiplexer (ROADM) using time-frequency domain processing. The proposed ROADM is realized by allocating wavelength channels and time slots to corresponding 2D spatial channels on a MEMS optical switch. Experimental results show the wavelength- and time-selective drop operation for a signal with equivalent 3.2 Tb/s (0.64 Tb/s × 5 channels), and the reconfigurability by the switching operation of the MEMS optical switch.